Peran AKal dan Kebebasan Bertindak dalam Filsafat Ketuhanan Mu'tazilah - Analiansyah Analiansyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Mu`tazilite is one of the Islamic theology schools. The school is quite different from the other schools such as of the Sunnite and of the Shi`ite. Due to its difference it is considered unique, mainly in the case of the role of intellect to find the truth and the freedom human act. Consider to human freedom and the power of intellect gifted by God, it is obliged to a Moslem to upgrade his intellect in solving his problems of life, not solely dependent on the taqdir or God’s determination. According to Mu`tazilte, through intellect, man is capable to exploit natural sources for the human benefits as he likes rather than he depends on the taqdir like a fatalistic point of view.